Itinerário terapêutico de pessoas com hanseníase em um município do interior do Ceará - Carneiro, Liana Maria Rocha (2019)
Leprosy is a chronic and infectious disease that mainly affects the skin and the peripheral nerves and has a slow and chronic evolution. It features a high disabling, stigmatizing power and it has a historical past of discrimination and isolation. The illness’ late diagnosis contributes to the worsening of symptoms and the onset of physical disabilities.Given the high rate of detection of the disease in Brazil, it remains a serious public health problem. Early diagnosis is the most efficient way to prevent installation of physical disabilities and incapacities. During the experience in the Family Health Strategy of the municipality of Quixadá-CE, the opportunity to care for the patient with leprosy was had, besides the identification of the long journey that users face, migrating through various professionals and services before the correct diagnosis. Therefore, this study aims to analyze the therapeutic itinerary of people with leprosy undergoing treatment in the municipality of Quixadá-CE, with focus on socioeconomic contexts and access to health services. Of cross-sectional, descriptive-exploratory and qualitative approach, the research was conducted in the municipality of Quixadá-CE. The population of this study was composed of 12 people who were undergoing treatment for leprosy in the months of June and July 2019, residing at the research site. Data collection occurred through individual interviews in a private environment, guided by a semi-structured form consisting of two blocks: sociodemographic and clinical data; and therapeutic itinerary. Data analysis was based on the Collective Subject Discourse (CSD) technique. To support the analysis of the data of this research, the free software IRAMUTEQ was used. The project for this investigation was submitted to the Research Ethics Committee of the Federal University of Ceará and approved under the opinion number 3.358.162. The therapeutic itinerary of leprosy patients in the municipality studied is a long and difficult route, such as delayed diagnosis or scheduling exams and specialists, lack of personal interest and, mainly, the lack of knowledge of some professionals.This path in search of diagnosis is characterized by several medical appointments in the Basic Health Units, which often unsuccessfully caused the user to seek private and specialized medical care. This search for different professionals is, in most cases, related to the lack of knowledge about the disease by some professionals. This essay showed that the therapeutic itinerary of leprosy patients in the search for diagnosis is long, confusing and with obstacles. It is indicative of how unprepared health professionals are and the need for training and consequent qualification for a better monitoring of the patient and their family. The patient must be monitored in full, aiming at the rescue of citizenship and respect for these people. The professional should act in a humane manner, advising on the disease, treatment, cure and, especially, work to deconstruct prejudice, always considering the values, opinions, knowledges and fears of these people.